A Case Study on ESG Performance: Brand Equity, Brand Love and Brand Respect in a South Korean Ski Resort - Xiaolong Zhou; Mingyue Zhang (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego)
Objective: This study aims to investigate the structural relationships between the environmental, social and governance (ESG) performance of ski resorts and their brand equity value, encompassing brand awareness, perceived quality, brand associations and brand loyalty, as well as how these factors influence brand love and brand respect. Design/Method/Approach: To achieve this a web‑based survey was conducted, and after eliminating outliers, data from a total of 390 responses were analyzed using the SPSS and AMOS statistical software packages. Findings: The research findings indicate a positive correlation between the Environmental, Social and Governance (ESG) performance of ski resorts and brand equity (comprising brand awareness, perceived quality, brand associations and brand loyalty). Moreover, within this relationship, there is a positive correlation between brand equity and the concepts of brand love and brand respect. Conclusions/ Recommendation: This study reveals that in the ski resort industry, superior environmental, social and governance (ESG) performance significantly enhances brand equity dimensions such as brand awareness, perceived quality, brand associations and loyalty. Additionally, the enhancement of these brand equity di‑ mensions further elevates consumer brand love and respect, highlighting their critical role in the branding of ski resorts. Originality/Value: This research underscores the significant impact of environmental, social and governance (ESG) performance on enhancing brand equity within the ski resort industry, linking sustainable practices to improved brand perception and loyalty. It provides valuable insights for industry stakeholders, demonstrating the tangible benefits of integrating ESG considerations into strategic and marketing initiatives, thereby enriching the literature on sustainable business practices in tourism.